2022
DOI: 10.1155/2022/9917877
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Traffic Violation Behaviors on Traffic Fatal Crashes Using Multilevel Models on Expressways

Abstract: This study is intended to explore the impact of traffic violation behaviors on traffic fatal crashes on expressways. Based on the generalized additive model method, for independent traffic violation data and traffic fatal crash data from the Traffic Administration Bureau of Anhui Provincial Public Security Department, the relationship among the violations and traffic fatal crashes was discussed. Applying the proposed multilevel analysis method, which can effectively show the evolution trend among traffic viola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Traffic infraction behaviors are one factor that contributes to road traffic crashes. According to studies, traffic offenses are a major source of crashes and fatalities in a number of nations, including China, Europe, and the United States (7). Understanding and correcting these violations can play an important role in lowering the number of road traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Traffic infraction behaviors are one factor that contributes to road traffic crashes. According to studies, traffic offenses are a major source of crashes and fatalities in a number of nations, including China, Europe, and the United States (7). Understanding and correcting these violations can play an important role in lowering the number of road traffic accidents.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively prevent fatal accidents, it is crucial to develop strategies grounded in a thorough understanding of the various contributing factors. These encompass a range of elements from human behavior and vehicle malfunctions to environmental conditions and broader macrosocioeconomic influences [3]. Recent extensive research has demonstrated a mutual coordination between road transportation and economics [4], highlighting how economic status can influence regional disparities in crash occurrences [5].…”
Section: Introductionmentioning
confidence: 99%